Detail design and fabrication of a small water transport vehicle - 219355 Mohd. Azni Md. Kasim (Skudai : Universiti Teknologi Malaysia, 2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2007